Use and Appreciation of Mycenaean Pottery in the Levant, Cyprus and Italy (ca. 1600-1200 BC) - van Wijngaarden, Gert Jan (Amsterdam Archaeological Studies, 2002)
Pottery made in the aegean during the Late Bronze Age has been found widely distributed in many parts of the Mediterranean. At some four hundred sites outside Greece, Mycenaean dinner and storage vessels, as well as some figurines have been discovered. As such, this class of archaeological artifacts constitutes one of the main sources by which to study Mycenaean trade and interregional contact. However, the role of pottery in international exchange during this period is not properly understood. That role depended on the patterns of consumption in the societies importing Mycenaean pottery. In this book, such patterns of consumption are investigated for the three areas with the largest amounts of Mycenaean pots: the Levant, Cyprus and Italy. For each of these areas, three sites have been selected for a detailed analysis of the cultural contexts of Mycenaean pots on a local level. Variations and similarities between these sites form the basis for a discussion of the cultural significance of this class of material in the region as a whole. The variations in the cultural significance of Mycenaean pottery in these areas show that the meaning of archaeological artifacts depends on the contexts in which they were used, discarded and rediscovered.